Fabrication and characterization of rare earth (Ce, Gd, and Y) doped ZrO2 based metal-insulator-semiconductor (MIS) type Schottky barrier diodes. (March 2020) - Sasikumar, K.; Bharathikannan, R.; Raja, M.; Mohanbabu, B.
Abstract: The 8 wt% rare earth (RE = Ce, Gd, and Y) doped zirconium dioxide (ZrO2 ) thin films were prepared on glass substrates by spin-coating technique and annealed at 600 °C. Also, the RE:ZrO2 based metal-insulator-semiconductor (MIS) type Schottky barrier diodes were fabricated. X-ray diffraction (XRD) patterns revealed the mixed phase of monoclinic and tetragonal ZrO2 for the RE:ZrO2 films, and the pure monoclinic phase for the undoped ZrO2 film. Because of the doping with RE ions, the crystallite size reduced with the increase of oxygen vacancies. The scanning electron microscopic (SEM) images exhibited the rod-shaped and square-shaped grains for the undoped ZrO2 and Gd:ZrO2 thin films, respectively. Elemental compositions were confirmed by the energy dispersive X-ray (EDX) analysis. The UV–vis analysis showed the lower transmittance for the RE:ZrO2 films with a reduced band gap (Eg ). The dc electrical conductivity (σdc ) was increased with the decrease of activation energy (Ea ) due to the RE doping. When compared to the Al/undoped ZrO2 /p-Si Schottky barrier diode, the Al/RE:ZrO2 /p-Si showed an improvement in the values of barrier height (ΦB ), ideality factor (n), and series resistance (RS ). Highlights: Rare earth (Ce, Gd, and Y) doped ZrO2 insulating layer based MIS type Schottky barrier diodes have been fabricated. The mixed phase of m-ZrO2 and t-ZrO2 is observed for the Gd:ZrO2 thin film with the smaller crystallite size of 4.640 nm. In Gd:ZrO2 film, the increase in reverse current density is owing to the presence of square-shaped grains with dislocations. A higher dc electrical conductivity (σdc ) is observed for the Gd:ZrO2 film. When compared to the Al/undoped ZrO2 /p-Si SBD, the Al/Gd:ZrO2 /p-Si SBD shows an improvement in the values of ΦB, RS, and n.